Culture as a moderator for the infusion of Web 2.0 technology: TAM vs WebQual - Hammerich, Westley (My University, 2012)
It is clear that the internet is being used more often for social interactions but the reasons why people adopt these newer technologies are still unclear. Over the last thirty years numerous adoption theories have been proposed however few account for the newer types of technology, such as social website usage. Purpose – The study will compare and contrast two different models of adoption to see if one model is better than the other in understanding the usage of social networking websites such as Facebook. At an organisational level the idea of extended usage of technology has been encapsulated in the construct of infusion of technology into a work place. The study will also show that infusion of technology may occur at an individual level of research. The argument is made that since national culture has been shown to affect usage, national culture may moderate the level of infusion that is found. Methodology – The study will use a quantitative methodology to survey potential (or actual) users of Facebook using a structured questionnaire. Since two adoption models are being tested, two questionnaires were developed and tested. The items for the questionnaires have been adapted from prior literature. Reliability and validity tests confirmed the scales from prior literature. The sample was selected from higher education institutions within the Johannesburg region .Specifically, students from the University of the Witwatersrand and the University of Johannesburg were invited to complete the questionnaires. The two questionnaires were mixed randomly between the students. Findings – It was found that the traditional technology acceptance model could better explain the usage of social networking websites when compared to the more modern WebQual framework. The study found that there is a strong positive relationship between usage and infusion. In line with the prior research on national culture moderating usage, the study found that national culture does moderate the relationship between usage and infusion. Implications – The study has a number of implications. Firstly, the research compared two models of technology usage. The study showed that the technology acceptance model was better at explaining the usage of social networking websites. Future research should focus on improving the TAM model and may result in better understanding the usage of social websites. Secondly, a set of scales are provided for future research which allow for the measurement of infusion at an individual level. These scales were tested for reliability and validity in two separate data collections and in both collections the scales met or exceeded the statistical requirements. Thirdly, the relationship between usage and infusion is seen to be moderated by national culture. This has 5 large implications for organisations and people who use Web2.0 as a medium for business. As an example, marketers could use the results in better understanding the usage of these types of websites, in the hope that it would allow for better targeting and placement of adverts. Lastly, the implications may extend beyond the context of the research. The study found a relationship between usage and infusion at an individual level of analysis. The relationship may exist in other areas of research which relate to Information systems including but not limited to Marketing (increasing the life cycle of products and increasing the value of customers through brand loyalty) and human resources (increasing employee efficiency through understanding peoples infusion of different types of technology). Research limitations – The research is limited to the sample that was achieved. The findings can be directly inferred to a similar sample base within South Africa, however cannot be generalised to samples of dissimilar natures. While the study used Facebook as a case, it should be cautioned that the results should not be generalised to other forms of social networking websites such as Twitter. Originality – The study is original in the following ways: Firstly, the study was conducted in South Africa where few other studies been found with a similar nature. Secondly, the study extended the thoughts on usage to the idea of infusion. Thirdly, two models were directly compared with independent data collections occurring. Fourthly, the relationship between usage and infusion is seen to be moderated by national culture. Both the relationship as well as the moderation effects has previously been empirically shown.
Keywords: Computer networks; Internet; Social aspects; Information technology; Online social networks